Identification of Student Errors In Solving Trigonometry Problems in Class X SMK Negeri 3 Palangka Raya - Dita, Alifya; Alihasan, Qodri; Haryani, Desti (JURNAL PENDIDIKAN, 2024)
This study aims to describe the errors and factors that cause students to make mistakes in solving trigonometry problems. This research is a descriptive research with a quantitative-qualitative approach. The data collection techniques in this study were tests and interviews. Based on the results of the study, the errors made by students were∶ (1) fact errors (68.55%), namely students did not write and incorrectly write the symbol or notation of the symbols "α" and "°" in trigonometry material, (2) concept errors (30.65%), namely students could not and incorrectly determine trigonometric comparisons and students did not understand and apply the relationship between special angles and trigonometric comparison formulas, (3) operation errors (53.23%), namely students are unable to complete root form operations correctly and incorrectly enter the value of trigonometric comparisons (4) principle errors (70.16%), namely students are wrong in applying the Pythagorean formula and cannot apply the trigonometric comparison formula. The causes of errors made by students in solving trigonometry problems are∶ (1) remembering, in the form of students' lack of ability to remember material that has been learned from simple to difficult material, (2) understanding, in the form of students' lack of ability to understand the content of previously learned material, and (3) applying, in the form of lack of ability to describe material that has been learned in new situations and involves the use of rules or principles.